WHY RISK WHY NOW? CONCEPTUAL PROBLEMS AROUND THE RISK PERCEPTION IN TOURISM INDUSTRY - Korstanje, Maximiliano Emanuel (Revista Brasileira de Pesquisa em Turismo, 2011)
Even though the risk perception theory has been coined by Cognitive Psychology and widely used during more than 40 years, only after September 11th 2001 the term risk was borrowed to tourism fields. The psychological and symbolic impacts that generated the WTC attacks drew the attention of many scholars concerned by the destination image. However, based on assumptions that need to be revisited, this body of knowledge rests on shaky foundations simply because its working definition of risk seems not to be correct. In addition, risk perception theory nourishes a discourse enrooted in a radicalized construction of otherness whose characteristics scare us. To some extent, risk perception theory in tourism has much to say but in fact some previous points should be previously discussed.